Direct Medical Costs of Tetanus, Dengue, and Sepsis Patients in an Intensive Care Unit in Vietnam - Hung, Trinh Manh; Van Hao, Nguyen; Yen, Lam Minh; McBride, Angela; Dat, Vu Quoc; van Doorn, H. Rogier; Loan, Huynh Thi; Phong, Nguyen Thanh; Llewelyn, Martin J.; Nadjm, Behzad; Yacoub, Sophie; Thwaites, C. Louise; et al. (Frontiers in Public Health, 2022)
Background Critically ill patients require complex clinical care by highly trained staff usually within a specialized intensive care unit (ICU) with advanced equipment. There is currently limited data on the costs of critical care in low- and middle-income countries. This study aims to investigate the direct-medical costs of key infectious diseases (tetanus, sepsis, and dengue) admitted to the intensive care unit (ICU) of a hospital in Ho Chi Minh City (HCMC), Vietnam, and explore how the costs and cost drivers can vary between the different infections. Methods We calculated the direct medical costs for patients requiring critical care for tetanus, dengue, and sepsis. Costing data (stratified into different cost categories) were extracted from the bills of patients hospitalized to the adult ICU with a dengue, sepsis and tetanus diagnosis that were enrolled in three studies conducted at the Hospital for Tropical Diseases in HCMC from January 2017 to December 2019. The costs were considered from the health sector perspective. The total sample size in this study was 342 patients. Results ICU care was associated with significant direct medical costs. For patients that did not require mechanical ventilation, the median total ICU cost per patient varied between US64.4 to US675 for the different diseases. In contrast, the costs were higher for the patients that required mechanical ventilation, with the median total ICU cost per patient for the different diseases varying between US2,590 to US4,250. The main cost drivers varied according to disease and its severity. Conclusion This study demonstrates the notable cost of ICU care in settings like Vietnam, and that future studies are needed to further evaluate the costs and economic burden incurred by ICU patients. The data also highlight the importance of evaluating novel critical care interventions that could reduce the costs of ICU care.